The Source of Output Growth: Productivity Performance in the Indonesian Crude Palm Oil Industry - Dyah Wulan Sari, Ph.D. (Science Press, 2021)
Indonesia has become the largest producer and exporter of crude palm oil commodities in the world. Therefore, the production of CPO turns out to be very greedy for land. There are any problems in production CPO, therefore the study aims to develop a conceptual framework of the source of output growth, whether driven by input or productivity growth, and to implement this concept by investigating the source of output growth in the crude palm oil industry in Indonesia. The investigation applies firm-level panel data and follows a quantitative approach using general method of moments to estimate the production coefficients and calculate the input and productivity growth. The result shows that the output growth of the crude palm oil industry does not lead in productivity growth driven. It seems to be driven by input growth, not by productivity growth. Since growth is still driven by input, the crude palm oil industry will be less competitive in the world market. The high world demand for crude palm oil commodities from Indonesia must be met by using more efficient input factors, optimizing production scale, and supporting technological progress. The government, therefore, must have strategies that are more competitive in the global market.